Comparison of Laproscopic Burnia Technique Versus Laparoscopic-Assisted Needle Herniotomy for Inguinal Hernia Repair in Female Pediatric Patients - Yasir Makki, Muhammad Saad Zulfiqar, Syed Asif Hussain Shah, Mushtaq Ahmad, Rao Riaz Ul Haq, Aizaz Haider Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Objectives: To compare operative outcomes of the Burnia technique versus laparoscopic-assisted needle herniotomy in female pediatric patients with inguinal hernias. Study Settings: Department of Paediatric Surgery, Sahiwal Teaching Hospital, Sahiwal. Duration of Study: From May 2023 to November 2023. Data Collection: This randomized controlled trial(RCT) was conducted on 80 female children aged 1–12 years with unilateral or bilateral inguinal hernias. Participants were randomized equally into two groups: Group A underwent laparoscopic-assisted needle herniotomy, while Group B received the Burnia technique. Operative time, recurrence, and scar visibility were recorded. Follow-up was conducted at 1 week, 1 month, and 3 months postoperatively to note the outcome of both techniques. Results: The mean operative time was significantly shorter in the Burnia group (25.43 ± 7.74 minutes) compared to the needle herniotomy group (30.99 ± 9.04 minutes; p = 0.004). Recurrence occurred in 10.0% of Group A and 2.5% of Group B patients (p = 0.166). Visible scarring was significantly lower in the Burnia group (17.5%) than in the needle herniotomy group (42.5%; p = 0.015). Conclusion: The Burnia technique is a safe and effective sutureless alternative with reduced operative time and improved cosmetic outcomes. Keywords: Burnia technique, pediatric hernia, laparoscopy, sutureless repair, needle herniotomy